THE IMPACT OF COVID-19 PANDEMIC ON TYPE 1 DIABETES MELLITUS INCIDENCE AND ITS CLINICAL PRESENTATION IN CHILDREN AND ADOLESCENTS: ONE CENTER’S EXPERIENCE - Stankovic, Sandra; Gocic, Zlatibor; Golubovic, Milan; Stojkovic, Milica; Miljkovic, Dusan; Stajic, Suzana; Ognjanovic, Andjela; Topalovic, Marija; Cvetkovic, Vesna; Saranac, Ljiljana; Manojlovic, Milena; Zivic, Sasa; et al. (Acta medicae Medianae, 2022)
The outbreak of the COVID-19 pandemic has a drastic impact on health systems. The aim of this research is to present the incidence and clinical picture of newly diagnosed diabetes in children in our institution during the first year COVID-19 pandemic and to compare data with previous years. A total of 41 children were newly diagnosed with T1DM1. There were two non-significant join point periods with an annual percentage increase (2007-2012: APC 8,94%), followed by a decrease (2012-2015: APC -6,88%) and a statistically significant increase (2015-2020: APC 14,20%). During COVID year there were larger number of newly diagnosed children, but without statistical significance. The percentage of children presenting with DKA in the time of T1DM diagnosis was significantly higher compared to pre COVID-19 period (84.8% vs 34.6%; p < 0.001). Our results suggest a potential diabetogenic effect of the COVID 19 infection. Larger trials with long term follow ups are needed. Drastic increase of DKA on T1DM onset during COVID year urge need for better prevention measures.